Impact of hyperbaric oxygenation on the efficiency of combined treatment for ovarian cancer - A. S. Dzasokhov (Опухоли женской репродуктивной системы)
The author’s findings suggest the higher efficiency of standard combined treatment for ovarian cancer in combination with chemotherapy and oxygen therapy.